Incidence and Risk Factors for Hypoglycemia During Fetal-to-Neonatal Transition in Premature Infants - Mitchell, Nikki A.; Grimbly, Chelsey; Rosolowsky, Elizabeth T.; O'Reilly, Megan; Yaskina, Maryna; Cheung, Po-Yin; Schmölzer, Georg M. (Frontiers in Pediatrics, 2020)
Objective: To determine the incidence and risk factors associated with neonatal hypoglycemia in the premature population <33 weeks’ gestation. Methods: This was a secondary retrospective analysis from previous infants enrolled in randomized controlled trials. A total of 255 infants <33 weeks’ gestation were born during the study period. Eight infants were excluded due to missing glucose or maternal data and 175 infants were analyzed. Main outcome measures: Primary outcome was hypoglycemia (blood glucose <2.6mmol/L) determined via glucose oxidase method on arterial or venous blood gas. Birth weight subgroups: small for gestational age (SGA, birth weight <10%ile for gestational age) and large for gestational age (LGA, birth weight >90%ile for gestational age). Maternal hypertension was systolic blood pressure >140mmHg. Results: 175 infants <33 weeks’ gestational age (89 male, 84 female) were analyzed. Hypoglycemia occurred in 59 infants (33.7%). Maternal hypertension (OR 3.07, 95% CI 1.51-6.30, p=0.002) was the sole risk factor for neonatal hypoglycemia. Protective factors for hypoglycemia included labor at time of delivery (OR 4.51, 95% CI 2.29-9.18, p <0.0001) and antenatal magnesium sulfate (OR 2.53, 95% CI 1.23-5.50, p=0.01). There were no significant differences between hypoglycemic and euglycemic infants in sex, gestational age, LGA infants, antenatal steroids, vaginal birth, or maternal diabetes. SGA infants were excluded from analysis due to sample size. Conclusions: Premature infants <33 weeks’ gestation have increased risk of hypoglycemia. Maternal hypertension increases hypoglycemia risk. Antenatal magnesium sulfate administration or labor at time of delivery decrease hypoglycemia risk.